Strategies and solutions to return to training for teams and elite athletes after lifting COVID-19 restrictions - Saffar Kohneh Quchan, A. H.; Kordi, M. R. (Asian Journal of Sports Medicine, 2020)
In late December 2019, Wuhan China reported the spread of a severe respiratory syndrome, now known as coronavirus disease 2019 (COVID-19). The disease spread rapidly worldwide and became an unprecedented pandemic (1). Numerous countries have used restrictions and quarantines to control the disease that affected many educational, social, economic, and sports activities, including sports events. With the start of the new year and the months of January-March, all international sports events, including the 2020 Tokyo Olympics and domestic leagues, were postponed to keep spectators, athletes, and coaches healthy, and training for teams and athletes at all levels has been suspended (1, 2). Closing of sports events and canceled training of players causes some changes in the physiological, lifestyle, and psychological aspects of athletes (3). This phenomenon has a negative effect on the athlete`s immune system, fitness, and performance. Because many competitions will be resumed after lifting the restrictions and considering many teams and athletes insist on starting training, the use of inappropriate training strategies and methods puts more pressure on athletes, increases the risk of injury, and even raises the risk of COVID-19 infection. Therefore, in this article, we will first take a look at the improper strategies and methods, then come up with the appropriate solutions and ways for returning to low-risk exercise programs.